Analysis of Tread ICRs for Wheeled Skid-Steer Vehicles on Inclined Terrain - Martínez-Rodríguez, Jorge Luis; Morales-Rodríguez, Jesús; García-Caicedo, Jesús Marcey; García-Cerezo, Alfonso José (IEEE, 2023)
The instantaneous centers of rotation (ICRs) for the two treads of skid-steer vehicles moving with low inertia on hard horizontal terrain almost remain with constant local coordinates, which allows to establish an equivalence with differential-drive locomotion. However, this significant kinematic relationship has not been analyzed yet on sloped ground. One relevant difficulty of studying ICR behavior on inclined terrain, even on a flat surface, is the continuous variation of pitch and roll angles while turning. To overcome this problem, this paper analyzes a dynamic simulation of a skid-steer vehicle on horizontal ground where gravity is substituted by an equivalent external force in such a way that pitch and roll are kept constant. Relevant tread ICR variations on inclined ground have been deduced, which have a significant impact on skid-steer kinematics. These new findings have been corroborated experimentally with a four-wheeled mobile robot that turns on an inclined plane.
Keywords: Vehículos; Dynamic simulations; Ground vehicles; Kinematics; Skid-steering; Sloped terrain